2014
DOI: 10.1177/0748730413517983
|View full text |Cite
|
Sign up to set email alerts
|

Bright to Dim Oscillatory Response of the Neurospora Circadian Oscillator

Abstract: The fungus Neurospora crassa constitutes an important model system extensively used in chronobiology. Several studies have addressed how environmental cues, such as light, can reset or synchronize a circadian system. By means of an optimized firefly luciferase reporter gene and a controllable lighting system, we show that Neurospora can display molecular circadian rhythms in dim light when cultures receive bright light prior to entering dim light conditions. We refer to this behavior as the “bright to dim osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The morning-specific core circadian transcription factor WCC is rhythmically inactivated by clock-dependent phosphorylation [ 39 , 40 ]. When the function of WCC is compromised light- or clock-dependent transcription is essentially abolished [ 22 , 41 , 42 ]. To identify genes that are potentially regulated by WCC we analyzed the transcriptomes of light-grown cultures of wt and ∆ wc2 strains by RNA-seq.…”
Section: Resultsmentioning
confidence: 99%
“…The morning-specific core circadian transcription factor WCC is rhythmically inactivated by clock-dependent phosphorylation [ 39 , 40 ]. When the function of WCC is compromised light- or clock-dependent transcription is essentially abolished [ 22 , 41 , 42 ]. To identify genes that are potentially regulated by WCC we analyzed the transcriptomes of light-grown cultures of wt and ∆ wc2 strains by RNA-seq.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon could be explained in two ways: RCO-1 participates in the control of circadian output pathways or it impairs core-clock function (and therefore output as well). To evaluate the latter proposal, the expression of a transcriptional reporter of the core clock (frq c-box -luc) (Gooch et al 2014b;Larrondo et al 2015; was analyzed along with overall levels of frq expression. Consistent with an earlier report (Zhou et al 2013) we found WC-1-independent and elevated expression of frq/FRQ in strains lacking RCO-1; however, in independent analyses conducted in two separate laboratories we were unable to reproduce the arrhythmicity previously reported for Drco-1 mutants (Zhou et al 2013; Liu et al 2015), using either stock strains from the Neurospora knockout project or the strain developed and utilized in the prior report (Zhou et al 2013).…”
Section: Discussionmentioning
confidence: 99%